EFEKTIVITAS COOPERATIVE GAMES DALAM MENINGKATKAN KETRAMPILAN SOSIAL ANAK TAMAN KANAK-KANAK (Tinjauan Psikologis) - Kibtiyah, Mariah (Jurnal Studi Agama dan Masyarakat, 2011)
The main purposeÂ  of this research was to find out the influence of cooperative games to increase the social skill of kindergarten students. In addition, this research was conducted to identify the difference between the social skill of those who received the treatment, and those who did not.The research subjects were 28 kindergarten students from B classÂ  or Big Zero, age 5-6 years old. Random assigment was applied to assign the subjects into experimental group (14 students) and control group (14 students). The social skill was measured by social skill scale.Pretest â Posttest Control Group Design was used as the experimental design of this research, and the data were analyzed by t â Test. The result showedÂ  there was a highly significant difference between the social skill of the experimental group and the control group (t = 10,191 ; p = 0,000). The experimental group showed higher social skill (Mean = 111,857) than the control group (Mean = 53,893).According to the research result, the cooperative games was effective in increasing the social skill of kindergarten students.